ALDH1A3 Accelerates Pancreatic Cancer Metastasis by Promoting Glucose Metabolism - Nie, Shuang; Qian, Xuetian; Shi, Mengyue; Li, Hongzhen; Peng, Chunyan; Ding, Xiwei; Zhang, Shu; Zhang, Bin; Xu, Guifang; Lv, Ying; Wang, Lei; Friess, Helmut; et al. (Frontiers in Oncology, 2020)
The aldehyde dehydrogenase 1 family member A3 (ALDH1A3) is a key enzyme associated with a variety of metabolic processes, including glucose metabolism. We recently uncovered that glucose metabolism played an essential role in promoting metastasis of pancreatic ductal adenocarcinoma (PDAC). As ALDH1A3 labels an aggressive subtype of PDAC, we hypothesized that ALDH1A3 functionally promoted PDAC metastasis via its metabolic effect on glucose metabolism. Expression of ALDH1A3 was detected in human PDAC tissues by immunohistochemistry. ALDH1A3 was knocked down or overexpressed in PDAC cells by either shRNA or overexpression vector. The functional roles of ALDH1A3 were characterized in vitro and in vivo. Transcriptional profiling via RNA-sequencing was used to explore the possible underlying molecular mechanisms. Glucose uptake, extracellular lactate and ATP production were measured to access the metabolic influence of ALDH1A3 on PDAC cells. We found that ALDH1A3 was associated with poor prognosis in PDAC patients. Functionally, ALDH1A3 promoted PDAC metastasis in vitro and in vivo. Further studies revealed that ALDH1A3 activated PI3K/AKT/mTOR signaling pathway and its downstream target-PPARγ (peroxisome proliferator-activated receptor gamma). This led to increased expression of HK2 (hexokinase 2), which subsequently enhanced glycolysis in PDAC cells. Additionally, pharmacological inhibition of PPARγ activity in ALDH1A3-positive cells impaired glycolytic genes expression, PI3K/AKT/mTOR activity and cellular glycolysis. In conclusion, ALDH1A3 promotes PDAC metastasis via its metabolic influence on glucose metabolism. PPARγ and its downstream PI3K/AKT/mTOR signaling pathway maybe involved in this process.